BUZZ GROUP DALAM MENINGKATKAN PERILAKU PEMBERIAN MP-ASI - Ruri Noor Aini; Yuni Sufyanti Arief; Ni Ketut Alit (Pediomaternal Nursing Journal, 2014)
Children aged 6-24 months is a very important to growing up. If the children doesn’t obtain nutrional food asneeded, then their golden period turning into critical period of growth now or later. The aim of this study was to identifyand analyze the effects of using buzz group as a media to change mother’ behavior in giving complementary foodto children aged 6-24 months. This study was using a pre-experiment design with a pre and post test. Its population weremothers who have children aged 6-24 months at Baby Health Centre of Kapasari Village. The sample were choosedthrough purposive sampling technique based on inclution and exclution criteria. The independent variable was buzzgroup, the dependant variable was mother’s behaviour. Data were collected by questionnaire that analyzed usingWilcoxon Signed Rank Test with alpha level ≤0,05 as a signification. The result of Wilcoxon Signed Rank Test showedthat this method affected the change in knowledge (p=0,004), attitude (p=0,034) and the actions (p=0,005). Healtheducation with buzz group as a method has influence on the mother’s behaviour in giving complementary feedingat Baby Health Center of Kapasari village and it can be used as a media by nurses to improve the mother's behavior inthe provision of complementary feeding in children aged 6-24 months. Further researcher is expected to have a longerresearch time to improve the quality of observing the mother's action in giving complementary feeding in children aged6-24 months